The Geoethics of Using Geospatial Big Data in Water Governance - Silva, César de Oliveira Ferreira [UNESP]; Matulovic, Mariana [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Springer Nature, 2021)
Geoethics encourage us to reflect dialectically on the consequences, opportunities, risks and benefits of our actions when using geotechnologies. This paper presents insights into how geoethics can guide more conscious and transparent decisions in the use of geospatial data in water management. The concepts of microethics and macroethics are also presented in the context of geoethics. Water governance must provide water security in terms of quality and quantity for all citizens, ensuring that everyone receives water (equity) with transportation methods that avoid losses (efficiency), maintain quality (responsibility) with forms of monitoring and control that equalize the freedom (autonomy) and power (representativeness) of all agents involved. Following the principles of ensuring autonomy, equity, responsibility, efficiency and representativeness, the use of geospatial data must be made in order to achieve these objectives. For this, geoethics has a crucial role in providing guidelines to decision makers and society for guiding them in an inclusive, equitable and transparent way. The self (microethics) and societal (macroethics) responsibility and geoethical implication is distributed to all the components that constitute the complex system to which they are inserted, in different degrees of importance in decision-making.
Keywords: Allocation; Geoethics; Guidelines; Risk; Social